Comparative evaluation of efficacy and safety of carboxymethylcellulose either alone or in combination with non-steroidal anti-inflammatory drug in the treatment of dry eye in a tertiary care teaching hospital - Sindhu, Saubhagya; Dutta, Shakti B.; Beg, Mirza A.; Mittal, Sanjeev K.; Gupta, Sushobhan D. (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Dry eye produces discomfort and reducedvision. The treatment of dry eyes has traditionally involved hydrating and lubricating artificial tears. The newer medications include non-steroidal anti-inflammatory drugs (NSAIDs) for the treatment of dry eye disorders. This study was designed to compare the effect of topical carboxymethylcellulose (CMC) alone or in combination with topical NSAID for the treatment of dry eye in a tertiary care teaching hospital. Methods: A total of 60 patients diagnosed with dry eye were enrolled for a study period of 1 year. Patient of either sex (male/female), age between 18 and 70 years, and all diagnosed cases of dry eye in ophthalmology outpatient department were selected. Patients (n=60) were stabilized on CMC for 2 weeks and thereafter divided into two groups. Group I (n=30) received only topical CMC; Group II (n=30) received CMC+NSAID. The patients were followed up to 12 weeks. Diagnostic tests included Schirmer’s test and tear break up time (TBUT). Ocular Surface Disease Index (OSDI) was used for assessing the Quality of Life. Analysis was done using GraphPad InStat software. p<0.05 was considered significant. Results: This was an open-label study revealing a mean age of 46.0±1.79 years. Females (56.67%) showed a significantly higher prevalence of dry eye symptoms compared to males (43.33%). The mean duration of illness was 1.95±0.16 years.Schirmer’s test, TBUT test values and OSDI score in Group I and Group II at 0 and 12 weeks revealed significant intragroup difference (p<0.0001). At 12 weeks intergroup comparison in Schirmer’s test value (p>0.05) and TBUT test value (p>0.05) showed no significant difference while OSDI score revealed significant difference (p<0.05). Burning, stinging, blurring of vision, photophobia, and hyperemia were among the common adverse effects seen. Conclusion: Both groups showed significant improvement in Schirmer’s test and TBUT test value and OSDI score at the end of the study. Intergroup comparison showed a significant difference with reference to OSDI score. Patients receiving NSAID reported more adverse effects.